2020
DOI: 10.1007/s11116-019-10077-9
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effect of life course events on modality type and the moderating influence of life stage

Abstract: Previous research has demonstrated the relevance of life events to explain changes in travel behavior. Less clear is the moderating role played by life stages on the relationship between life events and travel behavior. Our goal in this study is to explore how the influence of life events on travel behavior differs by life stage. We use data from a travel survey of faculty, staff and students at a US university. We define four life stages: millennials living in shared apartments or alone, millennials living wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…In contrast, relocating to Davis, California, which has an exceptionally high prevalence of cycling compared to the rest of the US, was associated with increased cycling [70]. This finding was confirmed in a subsequent quantitative study [104]. Some individuals moved to Davis specifically for the ability to cycle [70].…”
Section: Relocationmentioning
confidence: 73%
“…In contrast, relocating to Davis, California, which has an exceptionally high prevalence of cycling compared to the rest of the US, was associated with increased cycling [70]. This finding was confirmed in a subsequent quantitative study [104]. Some individuals moved to Davis specifically for the ability to cycle [70].…”
Section: Relocationmentioning
confidence: 73%
“…Kuhnimhof et al [28] point out such differences as individuals experience an increase in mobility due to the formation of long-term configurations with regard to residential and work location as well as social networks and habits. Janke et al [15] also highlight the influence of life stages on travel behavior in their study. Especially, life events (e.g., retirement, having children) trigger changes in travel behavior.…”
Section: Mobility Style Typologiesmentioning
confidence: 90%
“…In addition to activity-based segmentation, there are also approaches that focus only on mode choice. Their object is to study modality types [14,15] or the use of specific modes such as car use [16,17]. These approaches (activity and mode choice) focus mainly on indicators of everyday travel.…”
Section: Behavioral Typologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, evidence from the US found that obtaining a driver’s license at ages 16–18 years was associated with 40% decline in the number of walking trips [ 20 ]. Importantly, studies from the transportation field suggest that car users have the highest probability of ‘sticking’ to their travel mode compared to those who use multiple modes of travel (e.g., combination of walking and public transport) [ 21 , 22 ]. Therefore, it is important to promote active travel among adolescents before habitual car driving patterns are established.…”
Section: Introductionmentioning
confidence: 99%